MAKNA SEMIOTIKA PERANGKAT ADAT DALAM TRADISI MARPEGE-PEGE PADA MASYARAKAT BATAK ANGKOLA PADANGSIDIMPUAN - Sandra Hasibuan, Alika; Samuel Nugraha Cristy; Br. Perangin-angin, Alemina; Chunliu, Liao (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This research aims to determine the semiotic meaning of traditional devices in the ‘marpege-pege’ tradition in the Padangsidimpuan Batak Angkola. The method used in this research is the ethnographic method as determined by Spradley. Data was obtained through in-depth interviews with elements of society and “suhut” the elements or parties holding the event. The data analysis method used is de Sausure analysis (1859) by interpreting two dichotomies: signifier and signified. The results of his research show that there are 6 traditional devices that support the traditional “marpege-pege” procession. The semiotic meanings contained in the 6 traditional devices are “amak lappisan” which means a special seat, namely an entity that has a high position, “pinggan godang” and “haronduk” which means a respect, “Sipulut” (sticky rice) and “inti” (coconut mixed with brown sugar) which means to tighten. The relationship between the entities in the “marpege-pege” tradition, “Burangir” (betel), “soda”, “pining” (betel nuts) and “gambir” means a form of gratitude, “timbako” (tobacco) or (cigarette) has the meaning as a form of appreciation for community leaders who have present at traditional processions and “Abit” (cloth) has a simple meaning.